Diet Composition and Seasonal Fluctuations in the Feeding Habit of Snow Barbel (Schizothorax plagiostomus) in River Indus, Pakistan - Khan, Muhammad Qayash; Anjum, Muhammad Zubair; Akhter, Shamim; Khattak, Irfan; Ali, Abid (Acta Scientiae Veterinariae, 2018)
Background:Schizothorax plagiostomus is widely distributed in river Indus and is most important food fish in Pakistan. The feeding habit of fish is directly related to the size of fish, its metabolic rate and environmental temperature. The accurate description of fish diet and feeding habit is a very important aspect in fisheries management for the purpose of species conservation, breeding and culture. The present work was aimed to investigate the specie abundance, the diet composition and seasonal variations in the feeding habit of Snow barbell Schizothorax plagiostomus. Materials, Methods & Results: A total of 1799 fish specimens were caught at the confluence of six tributaries along river Indus at Indus Kohistan, northeastern Pakistan. The fish were collected by 5-panels of gill net during first week of each month. The site specific Catch Per Unit Effort (CPUE) and season specific CPUE of fish fauna were assessed. For the gut content analysis 240 samples (99 male and 141 females) of S. plagiostomus were selected on monthly basis. Frequency of occurrence method and volumetric method were applied to record the different food items in the gut of S. plagiostomus. The physico-chemical parameters, NO3 concentration and dissolved Co2 of water from different localities of river Indus were recorded month wise by Hach sensION 156 meter, Horiba LAQUA Nitrate Meter and EA80 meter respectively. Significant difference was observed in water temperature during the four seasons. Except alkalinity no other water parameter showed significant variation across different localities. The results showed that highest Mean CPUE was observed for Darel Stream (0.55) and lowest for Jalkot stream (0.26). Peak abundance of fish was recorded in the month of November with a mean catch of 44.50, mean CPUE of 0.74 and mean Kruskal-Wallis rank value of 63.25. Spirogyra and Ulothrix occurred as maximum food items in the gut of S. plagiostomus during summer while their minimum amount occurred during autumn. According to the ranking index spirogyra and ulothrix ranked higher with significant difference in comparison to other food items. The results showed that S. plagiostomus is phytophagous in its feeding habit, which consumed mainly algae attached to stones and pebbles during the whole year. However, the presence of some secondary items such as animal matter, detritus, sand and mud might be due to the distinct availabilities of food along the seasons. The highest feeding activity of S. plagiostomus was recorded during summer while the lowest one occurred during autumn, spring and winter. Discussion: Catch per unit effort (CPUE) is an indirect measure of the abundance of a target species. It is used as an index of stock abundance in fisheries and conservation biology. During the study low fish fauna was found in River Indus as reported previously. Majority of the fish occurred in snow fed river tributaries in the study area as these tributaries are comparatively less turbulent. Previous studies have also recorded that Schizothoracine generally prefer clean waters. The present findings of gut contents analysis showed clearly that S. plagiostomus is a phytophagous fish which scrap and consumed spirogyra and ulothrix attached to stones and pebbles. Earlier it was reported that mouth of S. plagiostomusis is inferior, wide, with deep lower jaw having keratinized cutting edge and the lower lip is folded and expanded with numerous papillae making it best suited for scrapping algae attached to stones and pebbles. The highest feeding activity was observed during warmer months as compared to cold months. S. plagiostomus spawn twice in a year in autumn and in spring. The highest feeding activity of S. plagiostomus seems to be link with a reflex of recovery strategy due to physiological process of gonadal development.